Schools of Democracy: A Political History of the American Labor Movement - Cantin, Étienne (Relations industrielles / Industrial Relations, 2007)
The article reviews the book, "Schools of Democracy: A Political History of the American Labor Movement," by Clayton Sinyai.
Keywords: American history; Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Politics; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z